Kajian Literatur Metode Pada Sistem Pendukung Keputusan Penentuan Dosen Berkinerja Terbaik - Nidya Kusumawardhany (Asosiasi Pendidikan Tinggi Informatika dan Komputer Provinsi DKI Jakarta, 2022)
Abstract— The purpose of this study is to describe a literature review on the determination or selection of lecturers with the best performance. The research method used is a qualitative research method with a literature review approach. The research steps begin with determining the topic, collecting journals with the chosen topic, analyzing the selected journals and making a review. The journals used as sources of research data were taken from 2015 to 2022 with the keywords